Symptomatic HPV-related neovaginal lesions in transgender women: case series and review of literature. (24th March 2016) - van der Sluis, Wouter B; Buncamper, Marlon E; Bouman, Mark-Bram; Neefjes-Borst, E Andra; Heideman, Daniëlle A M; Steenbergen, Renske D M; Mullender, Margriet G
Abstract : Objective: Worldwide, transgender women are an at-risk population for contracting sexually transmitted infections. Little information exists on symptoms and characteristics of neovaginal human papillomavirus (HPV) infections and associated diseases. We describe a case series of transgender women with symptomatic HPV-related neovaginal lesions and a review of current literature. Methods: Transgender women with symptomatic HPV-related neovaginal lesions were identified from a departmental database comprising clinical and outpatient data on transgender women who underwent vaginoplasty between 1990 and 2015. HPV status was determined on excision and biopsy specimens by HPV DNA testing using GP5+6+-PCR and p16 INK4A immunohistochemistry. Current literature was reviewed using the MEDLINE and EMBASE databases. Results: This case series includes four transgender women with symptomatic, HPV-related neovaginal lesions. Two women presented with neovaginal and neovulvar pain and condylomata/leukoplakia, which were excised. These lesions showed moderate-to-severe dysplasia at histopathological examination, and were positive for high-risk HPV (hrHPV) and p16 INK4A . Recurrence occurred in one patient and was treated with laser evaporation. Two women presented with neovaginal coital pain, neovaginal bleeding and condylomata. Neovulvar lesions were treated with podophyllotoxin. Neovaginal lesions were excised or evaporated. These lesions were low-risk HPV (lrHPV) positive. The literature search shows treatment options varying from conservative, topical podophyllotoxin to excision or laser evaporation under general anaesthesia. Conclusions: Neovaginal HPV infection can lead to benign condylomata (lrHPV) and various grades of dysplasia (hrHPV). We advise physicians to consider HPV infection and associated lesions in transgender women with otherwise unexplainable neovaginal pain or bleeding after vaginoplasty.